Determination of The Shortest Route Based on BFS Algorithm for Purpose to Disaster Evacuation Shelter - Sularno, Sularno; Mulya, Dio Prima; Astri, Renitra; mulya, Dwiki (Scientific Journal of Informatics, 2021)
Purus village in Padang City which has an area of 0.86 km2 consisting of 8 RW and 28 RT has a population of 8,075 people with a density of 11,875. As a result, people are always haunted by fear and always feel threatened if an earthquake occurs. If an earthquake and tsunami occur, what the community needs at that time is information about a safe zone that can be reached to save themselves and their families. For this reason, there needs to be an educational process for the community so that they have a culture of disaster awareness in the form of a system that is able to inform the community where the closest safe zone they can reach is the route they must take when a disaster strikes so that it can provide a sense of security because of safety guarantees. This study aims to determine the shortest route that can be taken by the user (community) during a disaster to reduce the risk of a greater number of victims by using the Breadth first search algorithm which is integrated into a web-based GIS application. By determining the starting point which is the user's position when the disaster occurs, and then determining the end point which is the location of the closest shelter, it will be possible to calculate the shortest distance that can be reached by the user at that time. The method chosen in this study is a waterfall because each step of the research carried out must be sequential and structured to avoid the risk of errors in each sequence of processes carried out. The results of this study can be proven by doing manual calculations to determine the shortest distance which will later be compared with the results of applications that have been designed using the BFS algorithm.